FACE AND POLITNESS STRATEGY APPLIED IN NANNY MCPHEE'S IN INDONESIAN SUBTITLE - Nuning Yudhi Prasetyani (Prasasti: Journal of Linguistics, 2016)
Politeness possibly affects both in speaking and an action in an interaction. It performs the speaker has a good moral. According to Yule (2000:60), “Politeness, in an interaction, can then be defined as the means employed to show awareness of another person‟s face.” Based on this theory, it tells how the speaker acts to conduct awareness of the other‟s face. Furthermore, the speaker will act carefully whenever he faces the addressee to respect his/her face, as the addressee has a higher status than the speaker. Additionally, politeness is divided into four strategies, positive politeness, on record, off record, and negative politeness. Each strategy has own way in interaction. This paper aims at investigating (1) What are the politeness strategies applied in the English and Indonesian subtitle in Nanny Mcphee and (2) What kind of translation procedures used in rendering English politeness strategies into Indonesian.